Case Report: Multiple Sclerosis Relapses After Vaccination Against SARS-CoV2: A Series of Clinical Cases - Nistri, Riccardo; Barbuti, Elena; Rinaldi, Virginia; Tufano, Laura; Pozzilli, Valeria; Ianniello, Antonio; Marinelli, Fabiana; De Luca, Giovanna; Prosperini, Luca; Tomassini, Valentina; Pozzilli, Carlo (Frontiers in Neurology, 2021)
Objective: To describe a temporal association between COVID-19 vaccine administration and multiple sclerosis (MS) relapses Methods: This case series study was collected in 4 MS Centres in Central Italy, using data from 16 MS patients who received COVID-19 vaccination and presented both clinically and radiologically confirmed relapses between March and June 2021. We collected patients’ relevant medical history, including demographics, MS clinical course, disease-modifying treatment (DMT) received (if applicable), and data from MRI scans obtained after the COVID-19 vaccination. Results: Three out of 16 patients received a diagnosis of MS with a first episode occurring after COVID-19 vaccination; 13 had already a diagnosis of MS and, among them, 9 were on treatment with DMTs. Ten patients received BNT162b2/Pfizer-BioNTech, 2 patients mRNA-1273/Moderna and 4 patients ChAdOx1 nCoV-19/Astrazeneca. All MS relapses occurred from 3 days to 3 weeks after receiving the first dose of the COVID-19 vaccination or the booster. All patients had evidence of radiological activity on MRI. Discussion: Clinical and radiological findings in these cohort of MS patients confirmed disease re/activation and suggested a temporal association between disease activity and COVID-19 vaccination. The nature of this temporal association, whether causative or incidental, remains to be established.